2008
DOI: 10.1016/j.brat.2008.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of hoarding behavior in a community-based sample

Abstract: Little is known about the prevalence and correlates of hoarding behavior in the community. We estimated the prevalence and evaluated correlates of hoarding in 742 participants in the Hopkins Epidemiology of Personality Disorder Study. The prevalence of hoarding was nearly 4% (5.3%, weighted) and was greater in older than younger age groups, greater in men than women, and inversely related to household income. Hoarding was associated with alcohol dependence; paranoid, schizotypal, avoidant, and obsessive-compul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
363
12
13

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 366 publications
(418 citation statements)
references
References 33 publications
30
363
12
13
Order By: Relevance
“…Consistent with HD prevalence reports from across the lifespan, we found that the majority of the participants were unmarried (Timpano et al, 2011) and that married participants were more likely to report lower hoarding severity (Samuels et al, 2008). Similar to prevalence reports of hoarding in community samples, there was no relationship between number of cohabitants and the cognition-related symptoms of HD, such as is measured by the UHSS and the SI-R (Samuels et al, 2008), although increased number of cohabitants led to decreased scores on the CIR, suggesting that as the number of people sharing a home increased, the clutter levels in that home actually decreased.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Consistent with HD prevalence reports from across the lifespan, we found that the majority of the participants were unmarried (Timpano et al, 2011) and that married participants were more likely to report lower hoarding severity (Samuels et al, 2008). Similar to prevalence reports of hoarding in community samples, there was no relationship between number of cohabitants and the cognition-related symptoms of HD, such as is measured by the UHSS and the SI-R (Samuels et al, 2008), although increased number of cohabitants led to decreased scores on the CIR, suggesting that as the number of people sharing a home increased, the clutter levels in that home actually decreased.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to prevalence reports of hoarding in community samples, there was no relationship between number of cohabitants and the cognition-related symptoms of HD, such as is measured by the UHSS and the SI-R (Samuels et al, 2008), although increased number of cohabitants led to decreased scores on the CIR, suggesting that as the number of people sharing a home increased, the clutter levels in that home actually decreased. Thus, being married and having more than one additional person in the home may serve as a buffer to clutter build up over time.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…For instance, hoarding has been associated with a number of personality disorders other than OCPD, including the paranoid, schizotypal, and avoidant personality disorders. [54][55][56] Also, it has been suggested that deleting hoarding and miserliness items from the set of OCPD criteria may improve the validity of the OCPD diagnosis. 57,58 Similarly, in longitudinal studies, only non-hoarding OCPD criteria, such as preoccupation with details, rigidity and stubbornness, and reluctance to delegate, were predictive of the diagnosis of OCPD two years later.…”
Section: Is Hoarding Different From Ocd and Ocpd?mentioning
confidence: 99%